The Study of the Credit System by the Method of Linear Graph - Fei, John C. H. (The Review of Economics and Statistics, 1960)
T HE study of the credit system is, traditionally, an important part of economic discipline. It is the purpose of this paper to introduce a new method, the method of the linear graph, for the study of this time-honored subject. Ostensibly, the contribution of this paper is pedagogical. However, this method enables us to identify and classify all transactions from properly constructed economic models of credit structures. Since all the operations of a credit system are formed of transactions, it is hoped that an axiomatic approach, which is conspicuous by its absence in the study of money and banking, can be initiated through this approach. In order to do this, certain elementary mathematical concepts of the linear graph must be introduced. For this reason, we shall proceed informally and omit all proofs in our presentation. However, the applicability of the mathematical theory of linear graph to the study of money and banking problems is by no mean limited to the elementary mathematical knowledge contained in the text. It is hoped that the method initiated in this paper can be further developed to yield more fruitful results in economic analysis. This is illustrated in the appendix by some examples of economic analysis using non-trivial theorems of linear graph. The text of this paper, however, can be read by readers with no mathematical background in linear graph theory.